Research of the Comprehensive Performance Test System of the RV Reducer Used in Robot - Lu Qi; Wu Xinhui; He Weidong (Jixie chuandong)
A kind of centring device and a comprehensive performance test system of the RV reducer used in the robot are provided,the test system including light transmission accuracy test module,load transmission accuracy test module,stiffness,backlash test module,precision life test module and transmission efficiency test module,the transmission accuracy,stiffness,backlash,precision life and the transmission efficiency of the RV reducer used in the robot with different series and different specifications could be highly accurately measured.The inspection standard for the design and manufacturing of the RV reducer used in the robot is provided,the higher percent of pass of the products before use is guaranteed,the inspection standard to improve the performance parameters of the RV reducer used in the robot is also provided.